2018
DOI: 10.1557/adv.2018.438
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Phosphonated Graphene Oxide and Sulfonated Poly(styrene-isobutylene-styrene) Composite Membranes

Abstract: Graphene oxide (GO) and its phosphonated analogue (pGO) have been incorporated into sulfonated poly(styrene-isobutylene-styrene) (SO3H SIBS) to generate membranes with enhanced water retention. The polymer nanocomposite membranes (PNMs) were prepared per SIBS sulfonation level (i.e., 38, 61, and 90 mole %), filler type (i.e., GO and pGO) and filler loading (i.e., 0.1, 0.5 and 1.0 wt.%). FT-IR and TGA confirmed the functionalization and incorporation of the fillers into SO3H SIBS. No significant changes were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The first region at approximately 100°C is attributed to the dehydration (i.e., loss of atmospheric moisture absorbed by the sulfonic groups) of the polymer. The second region in the 220–280 ° C range is attributed to the desulfonation (i.e., loss of the sulfonic groups) of the polymer and the third (410–430 ° C) to the degradation of the polymer backbone . Similar to other studies that incorporated fillers into SIBS or other polymers, the thermal stabilities of the membranes were unaffected by the incorporation of GO/sGO .…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The first region at approximately 100°C is attributed to the dehydration (i.e., loss of atmospheric moisture absorbed by the sulfonic groups) of the polymer. The second region in the 220–280 ° C range is attributed to the desulfonation (i.e., loss of the sulfonic groups) of the polymer and the third (410–430 ° C) to the degradation of the polymer backbone . Similar to other studies that incorporated fillers into SIBS or other polymers, the thermal stabilities of the membranes were unaffected by the incorporation of GO/sGO .…”
Section: Resultssupporting
confidence: 73%
“…Only the spectra for the maximum filler loading (i.e., 10 wt%) will be shown because no significant changes were observed in the PNMs at lower nanofiller levels. The spectra for SO 3 H SIBS show four bands at 1,151, 1,124, 1,034, and 1,007 cm −1 , which are representative of the stretching vibrations associated to the sulfonic group [37,42,44,45]. Therefore, overlapping occurs for the C-O, SO 3 H, and Si − O stretching vibrations of GO/sGO.…”
Section: Pnm Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Efforts have been focused on the addition of fillers that may decrease the methanol permeability of the membranes without significantly decreasing the proton transport . Avilés‐Barreto and Suleiman found that SO 3 H SIBS is suitable as a dispersant matrix for SWCNTs .…”
Section: Introductionmentioning
confidence: 99%
“…26 Efforts have been focused on the addition of fillers that may decrease the methanol permeability of the membranes without significantly decreasing the proton transport. 17,20,25,27,28 Avilés-Barreto and Suleiman found that SO 3 H SIBS is suitable as a dispersant matrix for SWCNTs. 25 Out of all the functionalizations performed to the SWCNTs, only sulfonation enhanced the performance of SO 3 H SIBS for DMFC and chemical and biological protective clothing (CBPC) applications.…”
mentioning
confidence: 99%